2013
DOI: 10.1111/gwat.12105
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ Sonication for Enhanced Recovery of Aquifer Microbial Communities

Abstract: Sampling methods for characterization of microbial communities in aquifers should target both suspended and attached microorganisms (biofilms). We investigated the effectiveness and reproducibility of low-frequency (200 Hz) sonication pulses on improving extraction efficiency and quality of microorganisms from a petroleum-contaminated aquifer in Studen (Switzerland). Sonication pulses at different power levels (0.65, 0.9, and 1.1 kW) were applied to three different groundwater monitoring wells. Groundwater sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…The significant shifts in community composition were not seen in this research, and the community composition appears to be closely aligned before and after sonication. The study by Ugolini et al (2014) found the alignment to the sediment (attached) profiles compared most closely when samples were collected immediately after sonication and the similarity reduced with time after sonication. They found that the timing of sampling for sonication appears to be important and should be undertaken as sonication is occurring (as was done in the present study) or immediately after.…”
Section: Resultsmentioning
confidence: 98%
“…The significant shifts in community composition were not seen in this research, and the community composition appears to be closely aligned before and after sonication. The study by Ugolini et al (2014) found the alignment to the sediment (attached) profiles compared most closely when samples were collected immediately after sonication and the similarity reduced with time after sonication. They found that the timing of sampling for sonication appears to be important and should be undertaken as sonication is occurring (as was done in the present study) or immediately after.…”
Section: Resultsmentioning
confidence: 98%
“…This suggests that spatial patterns of denitrification could be better resolved by sampling a denser well network or along distinct groundwater flow paths. Future karst denitrification studies may benefit from quantifying water sources near wells using end‐member mixing models and examining the potential importance of microsite denitrification through sampling of local biofilms using recently developed sonication sampling (Ugolini, Henneberger, Bürgmann, Zeyer, & Schroth, ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study can only affirm that nitrate reduction occurred, sometimes under conditions presumed unfavorable for nitrate reduction (oxic), with and without carbon addition, and that N functional gene expression data from porewater samples may not represent all of the nitrate reduction mechanisms occurring in the aquifer. Future work should focus on sampling of these biofilms using recently developed methods [ Ugolini et al ., ] and conducting experiments that directly investigate their influence on macroscale nitrate reduction mechanisms.…”
Section: Discussionmentioning
confidence: 99%